Workers experience guides Karaoke in Updating Status in Facebook as Interpersonal Relations and Personal Communication with Customers - Kiki Amelia Sari; Dra. Taufik Suprihartini, M.Si (Interaksi Online, 2016)
The presence of information technology is rapid and practical nature can allow for changes in behavior or lifestyle. One of them is the development of information technology with the birth of social networks, namely Facebook. Karaoke guide also actively uses Facebook to update your status and communicate with customers. By using qualitative methods, this study aims to describe the "Experience of Guides Karaoke Workers when Updating status on Facebook as Interpersonal and Personality Communication with Customers." This study uses an interpretive paradigm with data analysis techniques which refer to the phenomenological approach. Subjects consisted of three informants working as guides karaoke. The theory used is the theory of Computer Mediated Communication (CMC) Thurlow, Crispin. 2000) and New Media Theory (LittleJohn and Karen A. Foss.2011) Results from this study that the type of work that was involved by the informant is to be a guide karaoke are still actively use facebook. Activities conducted by informants in using facebook to update your status and get comments from customers. The informant made a status on facebook just to fill time while waiting for customers to come. As one of the self-actualization of the informants also upload photos on facebook as their identity is gorgeous to attract customer attention. Customers make personal communications more personal with the informants through other media such as via mobile phone by way of SMS or phone. Customers rarely use facebook as not free to chat on facebook. Customers are also free to contact the informant via sms or phone to ask her to meet, say hello, even if the customer is already close to'm accompanied by a meal together. The interesting thing was, between the customer and these informants there is a love or a relationship even though they were not long relationship. The study concluded that the informants use to update your facebook status and find new friends or new customers. The informant in communicating with customers not only through facebook but also use other media, namely via sms or phone because according to the informant if through facebook customers are not free to talk privately with the informants.